2014
DOI: 10.1097/icu.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Update on contraindications for laser-assisted in situ keratomileusis and photorefractive keratectomy

Abstract: Current contraindicatisons to LRS are based on FDA labeling and guidelines from the American Academy of Ophthalmology. Much of the evidence is based on case reports or series, anecdotal evidence, or known complications from nonlaser ocular surgery. More randomized clinical trials are needed to establish the safety of LRS in controversial conditions such as well controlled CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 45 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…Regarding corneal laser surgery, autoimmune or immune-mediated diseases should be considered relative contraindications, and uncontrolled diseases should be considered absolute contraindications due to the prevailing consensus. 9 Although Alió et al reported good final results following laserassisted in situ keratomileusis (LASIK) procedures for correcting refractive errors of two patients with CD and arthritis and 2 eyes of one patient with UC and arthritis, 10 the major issue was that corneal laser interventions could trigger melting or significant scar formation in patients with autoimmune diseases. Necrotizing keratitis followed by an uneventful LASIK procedure 11 can particularly raise difficulties since it may occur even in cases of stable and controlled IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding corneal laser surgery, autoimmune or immune-mediated diseases should be considered relative contraindications, and uncontrolled diseases should be considered absolute contraindications due to the prevailing consensus. 9 Although Alió et al reported good final results following laserassisted in situ keratomileusis (LASIK) procedures for correcting refractive errors of two patients with CD and arthritis and 2 eyes of one patient with UC and arthritis, 10 the major issue was that corneal laser interventions could trigger melting or significant scar formation in patients with autoimmune diseases. Necrotizing keratitis followed by an uneventful LASIK procedure 11 can particularly raise difficulties since it may occur even in cases of stable and controlled IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in visual acuity and spherical equivalent have been reported in eyes of women who became pregnant after LASIK [46]. Although pregnancy normally precludes corneal laser surgery [47], sometimes an early stage pregnancy has inadvertently not been identified. Also, traumatic corneal injury may require corneal surgery or other procedures involving wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the R124H mutation has also been described in clinically asymptomatic and “ dystrophy-free ” individuals prior to LASIK, who then develop deposition after LASIK [10, 11] suggesting this particular mutation and phenotype may be sensitive to/precipitated by/modified by trauma, genetic testing represents an important step especially in asymptomatic refractive surgery patients. Injury to the central cornea results in exacerbation of the GCD2 with dramatic acceleration of corneal deposition, opacities, and consequent visual loss.…”
Section: Discussionmentioning
confidence: 99%